PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING. (Studi Kasus pada Pelanggan ayam uleg cak abit) - Ismatul Ummah; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT In Indonesia, culinary was very developed and attracted by millennial in this era. Every year, there are many culinary is also a business that grows up that greatly with a variety of distinctive features and various variations since presentation and taste. Based on consumer needs and culinary development at this time also moving forward along the demands of market needs. The number of culinary is very much appreciated from domestic and abroad, this shows that the culinary business sector is experiencing very positive growth, especially in Malang. Furthermore, it is necessary to know what factors influence the level of customer satisfaction that business people can meet customer satisfaction. This present study aims to the effect of variable product quality, service quality, location price and satisfaction on customers' loyalty at the Ayam Uleg Restaurant. The population costumers of Ayam Uleg. The present study used 100 people as the sample. The data collection got from distributing questionnaires with purpose sampling techniques. The present study used Path Analysis, where Product Quality is X1, service quality X2, price (X3) location (X4) Y loyalty and satisfaction Z as the analyzed the data. The results of this study indicate that there is a positive and significant relationship between Product Quality, service quality, price and Location of Customer Loyalty through Satisfaction as an Intervening Variable. Keywords: Product Quality, Service Quality, Price, Location, Loyalty, Satisfaction.